Peningkatan Keterampilan Warga Desa Simo dalam Pengolahan Kedelai hingga Menjadi Produk Tempe Siap Konsumsi - Zulfatun - Anisah; Agus Wahyu Irawan; Laila Murningsih Novrian Wakhidah (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2025)
This community engagement program was implemented to address the issue of seasonal income instability experienced by the residents of Simo Village, most of whom rely on agriculture as their primary livelihood. Their economic condition becomes vulnerable during the non-harvest period, creating the need for alternative skills that can generate daily income. The program focused on enhancing the community’s ability to process soybeans into ready-to-consume tempeh—an activity that is easy to learn, requires low capital, and meets stable market demand. The main objective was to equip residents with technical skills in soybean processing while fostering the development of small household-based enterprises using local food resources. The activities employed the Asset-Based Community Development (ABCD) approach, emphasizing the identification, utilization, and strengthening of local assets through active community participation at every stage. The strategies included asset mapping, participatory planning, technical training on tempeh production, assistance in sanitation and marketing, and continuous evaluation. The results indicate a significant improvement in residents’ technical skills, the establishment of a tempeh producer group, behavioral changes related to hygiene and product quality, increased entrepreneurial motivation, and the emergence of local leaders who support program sustainability. Beyond providing direct economic benefits through daily income opportunities, the program also encouraged social transformation by strengthening social capital and fostering greater community self-reliance.